Temporal changes and clinical significance of peridevice leak following left atrial appendage occlusion with Amplatzer devices. Issue 7 (18th May 2022) - Korsholm, Kasper; Jensen, Jesper M.; Nørgaard, Bjarne L.; Nielsen‐Kudsk, Jens E.
Abstract: Background: The natural history of peridevice leak (PDL) following left atrial appendage occlusion (LAAO) is unknown. This study sought to investigate changes of PDL from 2 until 12 months after LAAO, using cardiac computed tomography (CT), and to assess the potential association between persistent PDL and clinical outcomes Methods: Single‐center observational study of Amplatzer LAAO implants between 2010 and 2017 ( n  = 206). Patients with 2 and 12 months cardiac CT were included in the study ( n  = 153). Images were blindly analyzed. PDL was characterized by frequency and size at the device disc, lobe, and left atrial appendage contrast patency. Patients were followed for the composite outcome of ischemic stroke, transient ischemic attack, systemic embolism, or all‐cause death. Median follow up from LAAO was 3.1 (2.3–4.3) years. Results: Contrast patency was present in 101 (66%) and 72 (47%) ( p  < 0.001) at 2 and 12 months, respectively. PDL was identified at the disc in 103 (67%) patients at 2 months versus 93 (61%) at 12 months ( p  = 0.08),  and at the lobe in 29 (19%) at both time points. PDL area at the disc did not change significantly over time, ∆ $\unicode{x02206}$ area: −8.95 mm (95% confidence interval [CI]: −18.9; 1.01) p  = 0.08. Permanent atrial fibrillation was independently associated with persistent PDL. Persistent versus no PDL was associated with a 62% worse clinical outcome, however not statistically significant, hazard ratio (HR): 1.62 (95% CI: 0.9–2.93), p  = 0.11. Conclusion: Persistent PDL was frequently observed following LAAO with Amplatzer devices. The PDL frequency and size appeared unchanged between 2 and 12 months. Persistent PDL was not significantly associated with worse clinical outcomes, yet this needs further delineation in future studies.